Vegetarian Diet in Chronic Kidney Disease—A Friend or Foe - Anna Gluba-Brzózka (Nutrients, 2017)
Healthy diet is highly important, especially in patients with chronic kidney disease (CKD). Proper nutrition provides the energy to perform everyday activities, prevents infection, builds muscle, and helps to prevent kidney disease from getting worse. However, what does a proper diet mean for a CKD patient? Nutrition requirements differ depending on the level of kidney function and the presence of co-morbid conditions, including hypertension, diabetes, and cardiovascular disease. The diet of CKD patients should help to slow the rate of progression of kidney failure, reduce uremic toxicity, decrease proteinuria, maintain good nutritional status, and lower the risk of kidney disease-related secondary complications (cardiovascular disease, bone disease, and hypertension). It has been suggested that plant proteins may exert beneficial effects on blood pressure, proteinuria, and glomerular filtration rate, as well as results in milder renal tissue damage when compared to animal proteins. The National Kidney Foundation recommends vegetarianism, or part-time vegetarian diet as being beneficial to CKD patients. Their recommendations are supported by the results of studies demonstrating that a plant-based diet may hamper the development or progression of some complications of chronic kidney disease, such as heart disease, protein loss in urine, and the progression of kidney damage. However, there are sparse reports suggesting that a vegan diet is not appropriate for CKD patients and those undergoing dialysis due to the difficulty in consuming enough protein and in maintaining proper potassium and phosphorus levels. Therefore, this review will focus on the problem as to whether vegetarian diet and its modifications are suitable for chronic kidney disease patients.